Synthesis and Characterization of Cellulose Acetate from Î±-Cellulose of Paper Waste - Ristika O Asriza; Nurhadini Nurhadini; Fardhan Arkan (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
A cellulose derivative substance called cellulose acetate is frequently used in the manufacturing of photographic film, fiber, membranes, and bioplastics. However, the availability of sources for cellulose acetate's raw material does not support this demand. Paper waste has a high cellulose content. Therefore, the aim of this research is to synthesize cellulose acetate from Î±-cellulose waste paper. In order to separate alpha cellulose from waste paper in this study, the delignification process with NaOH solvent was used as a first step. After obtaining alpha cellulose, acetic anhydride was used to carry out the acetylation reaction. The yield of Î±-cellulose from paper waste is 51.8%. Î±-Cellulose is reacted with acetic anhydride through acetylation reactions and hydrolysis of acetyl groups. From this reaction, functional groups -OH, C=O ester, and C-O acetyl appeared from the FTIR spectra analysis which indicated that cellulose acetate had been successfully synthesized. The type of cellulose acetate produced is a type of cellulose monoacetate with an acetyl groups of 23% and a degree of substitution value of 1.17.